Development of a novel database to review and assess the clinical effects of EPA and DHA omega-3 fatty acids. (August 2022) - Bernasconi, Aldo A; Wilkin, Allison M; Roke, Kaitlin; Ismail, Adam
Highlights: EPA/DHA are an active area of research. Each month, 200–250 new articles on EPA/DHA are indexed by PubMed. Despite a vast body of existing research, there remain significant gaps in our understanding of EPA/DHA health effects. The volume of existing research makes it challenging to conduct systematic investigations to identify or resolve those gaps. This article introduces the GOED Clinical Study Database (CSD), a comprehensive, manually curated database that catalogs this research. It also outlines the search strategies describes the methods for gathering data describes the database capabilities and current and potential applications. Abstract: Due to their multiple mechanisms of biological action, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) have been the focus of ongoing active research for decades. In spite of the resulting body of knowledge, there remain significant gaps in our understanding of EPA/DHA health effects. Further, the volume of existing research makes it challenging to conduct systematic investigations to identify or resolve those gaps. The purpose of this article is to introduce the GOED Clinical Study Database (CSD), a comprehensive, manually-curated relational database that catalogs this research.